PEMANFAATAN APLIKASI QUIZIZZ UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS 6 SDN 28 MELAYU KOTA BIMA PADA MATA PELAJARAN IPAS - Muhamad, Muhamad; Aliyyah, Rusi Rusmiati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Learning motivation is a crucial factor in achieving optimal learning outcomes, especially in Natural and Social Sciences (IPAS) subjects that require conceptual understanding and analysis. This study was motivated by the low interest in learning by 5th grade students of SDN 28 in IPAS lessons which is often caused by the delivery of material that is conventional and less interesting. Therefore, this study aims to analyze in depth the effectiveness of utilizing the Quizizz application as an interactive learning media in increasing student learning motivation in the subject. A descriptive qualitative approach was used to explore this phenomenon, with data collection techniques through participatory observation during learning, in-depth interviews with representative teachers and students, and analysis of learning outcome documentation. The subjects of the study were 25 5th grade students of SDN 28. The results of the study consistently showed that the implementation of the Quizizz application had a significant positive impact on increasing student learning motivation. Students' enthusiasm and active involvement in the IPAS learning process increased drastically. The gamification features offered by Quizizz, such as a point acquisition system, a real-time leaderboard display, and the presence of healthy competition elements between students, have proven effective in triggering interest and maintaining student focus. Teachers also reported an increase in two-way interactions in class and a better understanding of science concepts among students. These findings confirm that Quizizz is a gamification-based interactive learning media that has the potential to transform the learning atmosphere to be more fun and motivating, so that it can be an effective solution to overcome low student learning motivation. ABSTRAKMotivasi belajar merupakan faktor krusial dalam pencapaian hasil belajar yang optimal, terutama pada mata pelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) yang menuntut pemahaman konsep dan analisis. Penelitian ini dilatarbelakangi oleh rendahnya minat belajar siswa kelas 6 SDN 28 terhadap pelajaran IPAS yang seringkali disebabkan oleh penyampaian materi yang bersifat konvensional dan kurang menarik. Oleh karena itu, penelitian ini bertujuan untuk menganalisis secara mendalam efektivitas pemanfaatan aplikasi Quizizz sebagai media pembelajaran interaktif dalam meningkatkan motivasi belajar siswa pada mata pelajaran tersebut. Pendekatan kualitatif deskriptif digunakan untuk mengeksplorasi fenomena ini, dengan teknik pengumpulan data melalui observasi partisipatif selama pembelajaran, wawancara mendalam dengan guru dan siswa representatif, serta analisis dokumentasi hasil belajar. Subjek penelitian adalah 25 siswa kelas 6 SDN 28. Hasil penelitian secara konsisten menunjukkan bahwa penerapan aplikasi Quizizz memberikan dampak positif yang signifikan terhadap peningkatan motivasi belajar siswa. Antusiasme dan keterlibatan aktif siswa dalam proses pembelajaran IPAS meningkat drastis. Fitur-fitur gamifikasi yang ditawarkan Quizizz, seperti sistem perolehan poin, tampilan leaderboard secara real-time, dan adanya elemen kompetisi sehat antarsiswa, terbukti efektif memicu ketertarikan dan mempertahankan fokus siswa. Guru juga melaporkan adanya peningkatan interaksi dua arah di kelas serta pemahaman konsep IPAS yang lebih baik di kalangan siswa. Temuan ini menegaskan bahwa Quizizz merupakan media pembelajaran interaktif berbasis gamifikasi yang potensial untuk mentransformasi suasana belajar menjadi lebih menyenangkan dan memotivasi, sehingga dapat menjadi solusi efektif mengatasi rendahnya motivasi belajar siswa.